Presentation is loading. Please wait.

Presentation is loading. Please wait.

Expanding and Simplifying Algebraic Expressions x + x = 2x 2x - 5x = -3x 2(x + 1) + 3(x + 3) = 2x + 2 + 3x + 9 = 5x + 11.

Similar presentations


Presentation on theme: "Expanding and Simplifying Algebraic Expressions x + x = 2x 2x - 5x = -3x 2(x + 1) + 3(x + 3) = 2x + 2 + 3x + 9 = 5x + 11."— Presentation transcript:

1 Expanding and Simplifying Algebraic Expressions x + x = 2x 2x - 5x = -3x 2(x + 1) + 3(x + 3) = 2x x + 9 = 5x + 11

2 6 + (x - 1)(4) Four groups of (x - 1)

3 6 + (x - 1)(4) This is a zero model.

4 6 + (x - 1)(4) = 2 + 4x The simplified expression is 2 + 4x or 4x + 2. How can you use algebra tiles to show that 2 + 4x is the same as 4x + 2 ?

5 1.2x x x - 2x (x - 1) 4.-2 (x + 2) Simplify:

6 1. 2x x - 5 Simplify:

7 1. 2x x - 5 Simplify: zero = 6x - 2

8 2. x - 2x Simplify:

9 2. x - 2x Simplify: zero = -x - 6

10 3. 3 (x - 1) Simplify: = 3x - 3 How could you get this answer without using algebra tiles?

11 4. -2 (x - 2) Simplify: Step 1 2 (x - 2) Step 2 The opposite

12 4. -2 (x - 2) Simplify: 2 (x - 2) -2 (x - 2) = -2x + 4 How could you get this answer without using algebra tiles?

13 -2 (x - 2) + 3 (2x + 1) = -2x x + 3 = 4x + 7 Steps without algebra tiles How could you check your answer to see if it is equivalent to the original expression?


Download ppt "Expanding and Simplifying Algebraic Expressions x + x = 2x 2x - 5x = -3x 2(x + 1) + 3(x + 3) = 2x + 2 + 3x + 9 = 5x + 11."

Similar presentations


Ads by Google